Estudo comparativo das fezes e coprólitos não humanos da região arqueológica de São Raimundo Nonato, Sudeste do Piauí - Chame, Marcia (1988)
The identification of the zoological origin of coprolites still poses many questions in paleoparasitology where they provide one of most important research tools. Through the study of the characteristics of 39 samples of mammals faeces collected from 1984 to 1987 in the archaeological region of São Raimundo Nonato Southearn of Piauí, Brasil, and 6 samples collected in Zoological Garden, the criteria for the identification of faeces and coprolites were evaluated. The shape and macro-and-microscopic food contents, are characteristic features of the faeces of the local mammals. The use of size (width and length) of the faeces should be used with other parameters, as it influenced both by diet and size of th e animal. The parasites, when specific, may help the identification of the origin of the material, although their own identification is sometimes difficult. The colar of the rehydration solution has no di agnostic value as the same color can be observed in coprolites from distinct species, and faeces from different samples of the same species may show distinct coloration when rehydrateci. Based upon these criteria and on direct field observations, we were able to i dentify faeces from mammals belonging to the orders Carnivor a and Rodentia; families Cervidae and Tayassuidae: to the genus Alouatta and the species Tamandua tetradactyla, Kerodon rupestris, Galea spixii and Cerdocyon thous. Jaguar and puma faeces (Panthera onca and Felis concolor) could be distinguished from wild cat faeces. Throgh the criteria used to the identification of feaces from Kerodon rupestris and Tamandua tetradactyla, coprolites collected at the archeological site in the region were identified, by e comparison.